(untitled) (Colloquia Comparativa Litterarum, 2025)
This article examines two Balkan novels in which memories, as fragments woven into the textual fabric of the autobiographical, define the museum-like narrative structure. The focus of the comparative analysis is on the female voice, which dynamises the museum as a “place of memory” in the novel through the war theme. By replacing the lost home with a kind of a mobile ‘museum-novel’ (as a specific type of novel, the genre of exile), writers such as Gabriela Adameșteanu (Romania) and Dubravka Ugrešić (Croatia) problematize the image of the waiting woman Penelope, transforming their novels into a female Odyssey between personal and public, authentic and imaginary, past and present, continuity and discontinuity, myth and history.